2021
DOI: 10.3390/molecules26237293
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Potential Thrombin and Factor Xa Inhibitors from the Danshen–Chuanxiong Herbal Pair through a Spectrum–Effect Relationship Analysis

Abstract: In this study; a spectrum–effect relationship analysis combined with a high-performance liquid chromatography–mass spectrometry (LC–MS) analysis was established to screen and identify active components that can inhibit thrombin and factor Xa (THR and FXa) in Salviae Miltiorrhizae Radix et Rhizoma–Chuanxiong Rhizoma (Danshen–Chuanxiong) herbal pair. Ten potential active compounds were predicted through a canonical correlation analysis (CCA), and eight of them were tentatively identified through an LC–MS analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…GXNT is clinically used for treating CHD and ischemic cardiomyopathy with significant curative effects [ 13 ]. Our previous pharmacological experiments confirmed that GXNT has the functions of reducing whole blood viscosity, improving blood rheology abnormalities, antimyocardial ischemia, antithrombosis, and vasodilation [ 14 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…GXNT is clinically used for treating CHD and ischemic cardiomyopathy with significant curative effects [ 13 ]. Our previous pharmacological experiments confirmed that GXNT has the functions of reducing whole blood viscosity, improving blood rheology abnormalities, antimyocardial ischemia, antithrombosis, and vasodilation [ 14 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al prepared four kinds of Lichong Shengsui Yin extracts by different extraction methods and then mixed each extract in different proportions to prepare nine kinds of mixture and compared the anti-ovarian cancer activity of different component compatibility and the main active ingredients to play the efficacy through the spectrum-effect relationships [98]. Similar studies have also been conducted on the optimization of nine different ratios of Salviae Miltiorrhizae Radix et Rhizoma-Chuanxiong Rhizoma herbal pairs (1:0, 1:1, 2:1, 3:1, 5:1, 1:5, 1:3, 1:2 and 0:1) [99], and the optimization of extracts of Curcumae Rhizoma-Sparganii Rhizoma with different polar elution fractions (water, 20%, 40%, 60%, 80%, and 95% ethanol) [100]. In the optimization of component compatibility, one study used Fe 2+ instead of Hg 2+ to improve Zhusha Anshen Pill to create Tieshuang Anshen Prescription, which not only improved the sedative and hypnotic effect of the compound but also avoided the toxicity of Hg 2+ in the previous prescription [101].…”
Section: Pharmaceutical Process Optimization Of Tcmmentioning
confidence: 92%